Predictors of Malignancy in Patients of Extra Hepatic Biliary Obstruction - Manoria, Piyush; Noor, MT (International Journal of Innovative Research in Medical Science, 2023)
Background: Etiology of extra hepatic biliary obstruction (EHBO) is often a diagnostic dilemma. To differentiate between benign and malignant causes is of utmost important. Therefore, we conduct a study to know the various predictors of malignancy in it. Material and Methods: 138 consecutive patients diagnosed as EHBO were included in the study. After detail history, examination and investigations patients were divided into benign and malignant groups. Univariate and multivariate logistic regression analysis was done. Receiver operating characteristics curve was drawn to determine the optimal diagnostic cut- off value for predicting malignancy. Results: On univariate analysis patients with malignant EHBO were older, had more loss of weight, cholestatic symptoms, presence of hepatomegaly, palpable gall bladder, higher mean serum bilirubin [18.45±8.09 vs 9.70±9.40 mg/dl (p value <0.001)] and higher mean serum alkaline phosphatase [517.38±234.01 vs 356.44±208.98 IU/L (p value <0.001)]. Area under curve showed cut off value for serum bilirubin of >16.5 mg/dl (sensitivity 61.9%, specificity 84.3% and 95% confidence interval 0.751-0.896) and of serum alkaline phosphatase of >455IU/L (sensitivity 52.4%, specificity 82.9% and 95% confidence interval 0.651-0.824) as a predictor of malignancy. Multivariate analysis showed palpable gall bladder and serum bilirubin > 16.5 mg/dl to be independent predictors of malignancy. Conclusion: In patients with EHBO palpable gall bladder, serum bilirubin > 16.5 mg/dl and serum alkaline phosphatase > 455 IU/ L are important discriminating factors for malignancy.